Experimental support system for visual recognition and object nomination - Rodríguez Dueñas, W. R.; Marín Manrique, H.; Hernández Jaramillo, B. J.; Torres Narvaez, M.; Galindo Rojas, E. (Revista Mexicana de Ingenieria Biomedica, 2016)
A wide variety of stimuli or objects such as drawings or photographs are used in cognitive perceptual and language rehabilitation. However, the presentation of objects in three dimensions, due to the visual richness, facilitates the identification and could support the rehabilitation process. Objective. Design an experimental setup to determine the extent to which the modality of presentation of objects affects the visual recognition of objects. Materials and methods. A low-cost experimental system was designed in order to show the stimulus in three ways: images, videos and real objects. Eighty objects were selected and variables as manipulability, age of acquisition, familiarity, visual complexity, agreement on the label and lexical frequency were controlled. A pilot study was conducted using the system in five healthy participants and the reaction time to identify objects was measured. Results. The findings reveal that the differences in reaction times between the modalities of presentation support the influence of the mode of presentation in object recognition. Conclusions. The volume object properties could allow the exploration of characteristics that the photographs would not have. This may be why the reaction time to identify real objects or videos was lower. Low-cost alternatives for the visualization and object recognition are valuable in cognitive-perceptual and language rehabilitation.